Cosmology in contemporary public sculpture / Mahizan Hijaz Mohammad ... [et al.] - Mohammad, Mahizan Hijaz; Omar, Aznan; Baharom, Mohamad Khairi; Amir, Nur Muhammad Amin Hashim; Mazlan, Hilal (Universiti Teknologi MARA, Perak, 2022)
The aim of this paper is to study the aspect of cosmological characteristic that relates to the contemporary art works of Ramlan Abdullah. His art work entitled ‘Connectivity’ is currently exhibited at the Laman Seni Arca located at the premises of UiTM Seri Iskandar, Perak. The public artworks consist of five constructed tubular aluminium and stainless-steel structure that were created in massive scale. Each sculpture represented the artist passion and artistic experience in life ranging from tittle such as Ayden, Aydan, Sundial, seed and Double Disc. Meanwhile, Cosmology has always been an interesting part of human exploration and investigation on the mystery of the universe. It has been explored by many and has been referred to since the invention of traditional art of the Malays. In the practice of Malay custom, cosmology has been observed and appreciated as apart of Malay tradition. This paper will study on the relations and aspect of cosmology that underlying contemporary public art work. The formalistic and contextual part that relates to this and the elements that connected to it. It will focus on the method of observation through visual preferences and discussion on art appreciation according to Feldman model of Art criticism. The study will provide information on characteristic of elements that relates to cosmology and contemporary public art.